New records of eriophyoid mites from Iran (Acari: Trombidiformes: Eriophyoidea) and a description of a new Brevulacus Manson species - Soika, Grażyna; Gol, Ali; Honarmand, Arash; Wozińska, Anna; Sadeghi, Hussein (Zootaxa, 2017)
Four species of eriophyoid mites are recorded from Iran, of which three represent new records and the other is a new species. These species are: Brevulacus salicinus n. sp. (Diptilomiopidae), found on Salix sp. (Salicaceae); Aceria wallichianae Keifer, 1975 from Ulmus minor (Ulmaceae); Aceria granulata Carmona, 1972 from Verbascum spp. (Scrophulariaceae) and Tegnacus unicornutus Pye, 2012 from Carpinus betulus (Betulaceae). Each of these species are illustrated and provided with data regarding their distribution and host plants.